Design and development of a three-phase off-board electric vehicle charger prototype for power grid voltage regulation. (15th August 2017) - Yong, Jia Ying; Fazeli, Seyed Mahdi; Ramachandaramurthy, Vigna K.; Tan, Kang Miao
Abstract: This paper discussed the design and development of a 2 kVA three-phase off-board electric vehicle charger prototype with a practical voltage control, where the procedures of the experimental construction were comprehensively presented. For the experimental setup, the effectiveness of the interface circuits and auxiliary power supply units were individually validated. Moreover, the electric vehicle charger utilized a Digital Signal Processor to employ the control strategies of vehicle charging and power grid voltage regulation. The proposed control can simultaneously charge the battery of electric vehicle, maintain a constant DC-link voltage and also provide the appropriate reactive power compensation to regulate the grid voltage to the desired level. While complying with the power quality standards, the experimental results had validated the practicality of the integrated electric vehicle charger and the control performance. The charger prototype had effectively regulated the grid voltage to the pre-charge voltage of 0.96 per unit while maintaining the DC-link voltage at 150 V during various charging currents of up to 5 A. Highlights: Comprehensive procedures for the experimental setup of an electric vehicle charger. Design of a power grid voltage control utilizing reactive power compensation. Performance validation of the sensor and gate driver interface circuits. Experimental validation of the grid voltage regulation and vehicle charging control. Verification of the charger prototype in compliance with the harmonics standards.